The effects of employee satisfacton and performance appraisal on perceived job performance of academics in Khyber Pakhtunkhwa, Pakistan - Khan, Muhammad Asad (2019)
when dealing with its academic staff. Therefore, this requires the institutions‘ management to have an effective performance appraisal system, in order to evaluate and increase the job performance of their academics. Despite this, minimal research has examined the relationship between performance appraisal and perceived job performance among academics in the context of public universities of Khyber Pakhtunkhwa, Pakistan. The current study examined effects of employee satisfaction and performance appraisal on perceived job performance among academics in the target population based on procedural justice theory, expectancy theory and goal-setting theory. Quantitative research approach along with cross-sectional research design has been used to collect data from 301 academic staff in the target population through a self-administered questionnaire. The results of the current study provide empirical evidence on key issues related to performance appraisal of academics in the selected public universities. Findings have shown that fairness, untrained rater, rating scale format, goal-setting and purposes of performance appraisal and employee satisfaction are the potential hindering factors for low job performance in the respective universities. This research also gives clear directions to stake holders and policy makers on the existing performance appraisal system for improvement of the perceived job performance of academics in the public universities.